Exact solutions of coupled burgers equation with time-and space-fractional derivative - Elzaki, Salih M. (International Journal of Applied Mathematical Research, 2015)
In this paper, He’s projected differential transform method (PDTM) has been used to obtain solution nonlinear coupled Burgers equation. This method involves less computational work and can, thus, be easily applied to initial value problems. (PDTM) is used to determine the exact solutions of some nonlinear time and space–fractional partial differential equations. A number of illustrative examples are provided and compared with the other methods. The numerical results obtained by these examples are found to be the same.